THE ROLE OF PEDAGOGY IN THE HOSPITAL SCOPE AND ITS CONTRIBUTIONS: A BRIEF REPORT OF THE LITERATURE - da Silva dos Santos, Jozelenita; Antonio Jackson Paiva, José; Sousa Andreza, Raul; Ivoneide Benecio Malaquias Alves, Francisca (Health and Society, 2023)
This work aimed to deepen the studies regarding the role of Pedagogy in the Hospital context and its Contributions. This work is divided into three chapters: the first presents a brief historical account of pedagogy in the Hospital environment in Brazil and the World, ‘’ the second goes deeper into the importance of pedagogy and its contribution in the hospital environment, finalizing the last chapter of the work of pedagogue and his experiences in the hospital. Making it possible to understand the need for intervention by the pedagogue from the existing point of view with an analytical look, positive or negative. objective, the well-being of children or users suffering from illness. With the support of theoretical references, the work clarifies the course of this educational area in Brazil, the Legal Bases that guide the theme, relationships between hospital educators and children, and the pedagogical projects existing in the Youth Children’s Hospital. The related research is called qualitative, the importance that Hospital Pedagogy exerts in hospitals, often helping in the treatment of children/adolescents.